Knowledge management in two universities before and during the COVID-19 effect in Peru - Arias Velásquez, R.M.; Mejía Lara, J.V. (Elsevier, 2021)
Knowledge management evaluation is an important and complex problem in Peruvian universities. An efficient policy in knowledge management is a critical success factor and will also advance teaching and research. Likewise, innovation is a key resource for the well-being of national economies and international competitive advantage, especially with COVID-19 9 restrictions. This research article has demonstrated that an assessment of knowledge management (KM) capability in two private universities could be used for an efficient policy, in order to obtain the best result in knowledge management maturity. Having discussed how to construct a model for KM, the final section of this paper addresses ways of the incorporation of this technology in the society. The case study has been developed in Lima, associated to two universities with 271 teachers and 5928 students; with this model could be used for KM assessment in all university in Peru. This study uses the “Intellectus Model, Mejia model organizational knowledge capability areas and Knowledge Management Capability Assessment (KMCA) model for the assessment, before and during COVID-19. Our findings have demonstrated the university performance and challenges associated to knowledge management during COVID-19, the new policy for virtual instructions and digital transformation of the educational process have improved the cost efficiencies. However, this system also has a number of serious drawbacks and challenges in innovation, researching, connections with industry and academy; this 2021 requires a new perspective in innovation with a knowledge management scheme in Peruvian universities.
Keywords: Knowledge management; Maturity (psychological); Construct (python library); Critical success factor; Business; Knowledge economy; Capability Maturity Model; Coronavirus disease 2019 (COVID-19); Competitive advantage; Process (computing); Computer science; Political science; Marketing; Medicine; https://purl.org/pe-repo/ocde/ford#5.02.03